A high-performance 35CrMo steel stud based on sub-temperature quenching process and a preparation method thereof
By adopting sub-temperature quenching process and laser cladding technology on 35CrMo steel studs, the problems of insufficient low-temperature toughness and insufficient comprehensive performance are solved, and higher strength, wear resistance and high-temperature resistance are achieved, which are suitable for a wider range of application scenarios.
Patent Information
- Application Number
- CN202411271771.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-11
AI Technical Summary
When existing 35CrMo steel studs are used in low-temperature toughness and harsh environments, the comprehensive performance (such as strength, wear resistance, oxidation resistance, high temperature resistance, etc.) cannot meet higher requirements.
The heat treatment method based on sub-temperature quenching process is adopted, combined with homemade quenching liquid and ultrasonic assistive technology, and further prepare a composite laser cladding layer on the surface of the steel stud to improve its comprehensive performance.
It significantly improves the toughness and strength of the 35CrMo steel stud, enhances its surface wear resistance, oxidation resistance, high temperature resistance and corrosion resistance, thereby extending its service life and adapting to more use scenarios.
Smart Images

Figure CN119082426B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fastener processing, and in particular to a high-performance 35CrMo steel stud based on a sub-temperature quenching process and a preparation method thereof. Background Art
[0002] 35CrMo alloy structural steel has high static strength, impact toughness and high fatigue limit, higher hardenability than 40Cr, high creep strength and endurance strength at high temperature, and long-term working temperature can reach 500℃. Based on these excellent properties, 35CrMo steel can be used to manufacture fasteners, such as steel studs, which can be used in high-temperature working environments, such as boiler studs, engine studs, etc. However, the low-temperature toughness of 35CrMo steel is insufficient, and when used in some harsh environments, higher requirements are placed on its comprehensive properties (such as strength, wear resistance, oxidation resistance, high temperature resistance, etc.).
[0003] Sub-temperature quenching refers to quenching in a temperature range slightly lower than the lower limit of the material quenching temperature, which can significantly improve the toughness of steel, reduce the brittle transition temperature, and reduce high-temperature tempering brittleness. Combined with sub-temperature quenching, the use of a suitable heat treatment process can improve the comprehensive performance of 35CrMo steel. For example, patent CN108823361B discloses a processing method for refining 35CrMo alloy steel grains, which uses a process combining ultrasonic bonding and sub-temperature quenching to refine grains and improve the comprehensive performance of alloy components. However, it does not improve the wear resistance, oxidation resistance, and high temperature resistance of 35CrMo alloy steel.
[0004] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-performance 35CrMo steel stud based on a sub-temperature quenching process and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: in a first aspect of the present invention, a high-performance 35CrMo steel stud based on a sub-temperature quenching process is provided, which comprises a steel stud body and a composite laser cladding layer arranged on the surface of the steel stud body;
[0007] The composition of the steel stud body is calculated by mass percentage:
[0008] C: 0.32-0.40%, Si: 0.17-0.35%, Mn: 0.42-0.63%, Cr: 0.93-1.08%, Mo: 0.17-0.25%, Ni: 0.14-0.28%, Ti: 0.09-0.25%, the balance is Fe and unavoidable impurities;
[0009] The steel stud body is obtained by melting, casting, heat treatment based on sub-temperature quenching and machining, and the composite laser cladding layer is prepared on the steel stud body by a laser cladding process using composite cladding alloy powder as a cladding material.
[0010] A second aspect of the present invention provides a method for preparing a high-performance 35CrMo steel stud based on a sub-temperature quenching process as described above, comprising the following steps:
[0011] S1. Melting:
[0012] Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1450-1550℃ for 30-50min, slag off, LF refining, the refining temperature is 1520-1580℃, and the insulation time is 8-20min;
[0013] S2, casting: casting at 1400-1450°C to obtain a stud blank;
[0014] S3. Heat treatment based on sub-temperature quenching:
[0015] S3-1, high temperature normalizing and tempering: normalize the stud blank at 900-1000℃ for 1.5-4h, then cool to 500-600℃, temper for 2-6h, add to quenching liquid, and quench to room temperature with ultrasonic assistance;
[0016] S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace, kept warm for 35 minutes, then added to the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 550-600°C for 1-4 hours, and air-cooled to room temperature to obtain a heat-treated stud blank;
[0017] S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate;
[0018] S5. Laser cladding treatment:
[0019] After preheating the stud intermediate, composite cladding alloy powder is used as cladding material. A composite laser cladding layer is prepared on the surface of the preheated stud intermediate by synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud.
[0020] Preferably, the composition of the quenching liquid is as follows by weight percentage: 0.25% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water.
[0021] Preferably, the quenching liquid is prepared by:
[0022] 2 g of multi-walled carbon nanotubes were added to 100 mL of a mixed acid consisting of 95% by mass sulfuric acid and 60% by mass nitric acid in a volume ratio of 2:1, heated under reflux at 80°C for 12 h, cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 12 h to obtain modified carbon nanotubes;
[0023] According to the mass ratio, the modified carbon nanotubes were first added into deionized water, and ultrasonically dispersed for 60 minutes. Then, sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol were added under continuous stirring at 800 rpm, and ultrasonically dispersed for 30 minutes to obtain the quenching solution.
[0024] Preferably, the raw materials of the composite cladding alloy powder include, by weight percentage:
[0025] CeYO-Ni@TiCN powder 68-73%, Al powder 4.2-5.5%, Ti powder 5.8-7.4%, and the balance Ni powder.
[0026] Preferably, the preparation method of the composite cladding alloy powder is:
[0027] Al powder, Ti powder, Ni powder and CeYO-Ni@TiCN powder were added into a ball mill, and ball milled for 8 hours at 500 rpm under nitrogen protection, with a ball-to-material ratio of 8:1. After the ball milling, the composite cladding alloy powder was obtained;
[0028] Among them, the particle sizes of Al powder, Ti powder and Ni powder are all 0.5-5 μm.
[0029] Preferably, CeYO-Ni@TiCN powder is prepared by the following method:
[0030] 1) Ceramic particle pretreatment
[0031] TiC powder and TiN powder are respectively added to nitric acid with a concentration of 50-65wt%, ultrasonically treated for 15-60min, filtered, washed with deionized water until neutral, and then vacuum dried at 80-110°C to constant weight to obtain pretreated TiC powder and TiN powder;
[0032] 2) 0.65-2.62 g of pretreated TiC powder and 0.98-3.94 g of pretreated TiN powder were added to 50-200 mL of 0.25-1 mol / L NiCl2 solution, and then 4.6-18.4 mL of 0.05-0.2 mol / L CeCl3 solution and 11.2-44.8 mL of 0.05-0.2 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 30-90 min, and then the pH value was adjusted to 5-6 with 10-25 wt% hydrochloric acid;
[0033] 3) Under continuous stirring at 100-400 rpm, 65-260 mL of a 0.25-1 mol / L (NH4)2C2O4 solution is added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system is controlled to 50-60°C, the addition is completed within 1-4 hours, and then the reaction is continued for 1.5-4 hours, filtered, the solid product is washed with deionized water until neutral, and vacuum dried at 80-100°C to constant weight to obtain a precursor;
[0034] 4) calcining the precursor in a hydrogen atmosphere at 650-720° C. for 1.5-6 h, and grinding to obtain CeYO-Ni@TiCN powder.
[0035] Preferably, CeYO-Ni@TiCN powder is prepared by the following method:
[0036] 1) Ceramic particle pretreatment
[0037] TiC powder with a particle size of 1-3 μm and TiN powder with a particle size of 1-3 μm were added to nitric acid with a concentration of 55 wt%, and ultrasonically treated for 40 min, filtered, washed with deionized water until neutral, and then vacuum dried at 100° C. to constant weight to obtain pretreated TiC powder and TiN powder;
[0038] 2) 1.31 g of pretreated TiC powder and 1.97 g of pretreated TiN powder were added to 100 mL of 0.5 mol / L NiCl2 solution, and then 9.2 mL of 0.1 mol / L CeCl3 solution and 22.4 mL of 0.1 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 45 min, and then the pH value was adjusted to 6 with 20 wt% hydrochloric acid;
[0039] 3) Under continuous stirring at 200 rpm, 130 mL of 0.5 mol / L (NH4)2C2O4 solution was added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system was controlled to 55°C, the addition was completed within 2 h, and then the reaction was continued for 2 h, filtered, and the solid product was washed with deionized water until neutral, and vacuum dried at 90°C to constant weight to obtain a precursor;
[0040] 4) The precursor was calcined at 680°C for 3 h in a hydrogen atmosphere and ground to obtain CeYO-Ni@TiCN powder.
[0041] Preferably, the method for preparing high-performance 35CrMo steel studs based on the sub-temperature quenching process comprises the following steps:
[0042] S1. Melting;
[0043] Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1500℃ for 45min, skim off the slag, LF refining, the refining temperature is 1550℃, and the holding time is 15min;
[0044] S2, casting: casting at 1450° C. to obtain a stud blank;
[0045] S3. Heat treatment based on sub-temperature quenching:
[0046] S3-1, high temperature normalizing and tempering: the stud blank is heated to 950℃ at a rate of 20℃ / min, kept at this temperature for 2h for normalizing, then cooled to 580℃ at a rate of 15℃ / min, kept at this temperature for 4h for tempering, added to the quenching liquid, and quenched to room temperature under the assistance of ultrasound;
[0047] S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace, kept warm for 35 minutes, then added to the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 560°C for 2 hours, and air-cooled to room temperature to obtain a heat-treated stud blank;
[0048] S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate;
[0049] S5. Laser cladding treatment:
[0050] The stud intermediate was heated to 200°C and kept warm for 1.5 hours. Then, a composite cladding alloy powder was used as the cladding material. A composite laser cladding layer was prepared on the surface of the preheated stud intermediate by a synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud.
[0051] The laser cladding process conditions are: Ar gas is used as the protective gas, the flow rate is 10L / min, the laser power is 2.2kW, the spot diameter is 4mm, and the powder feeding amount is 15g / min.
[0052] Preferably, in step S3-2, the heating and holding procedure of the sub-temperature quenching is: heating to 765°C at a rate of 18°C / min, holding for 10 minutes, heating to 782°C, holding for 20 minutes, cooling to 770°C, holding for 5 minutes;
[0053] In step S3-1, the ultrasonic power for auxiliary quenching is 400-800W, and the ultrasonic frequency is 15-23kHz.
[0054] In step S3-2, the ultrasonic power for auxiliary quenching is 600-1000W, and the ultrasonic frequency is 18-24kHz.
[0055] The beneficial effects of the present invention are:
[0056] The present invention provides a high-performance 35CrMo steel stud based on a sub-temperature quenching process and a preparation method thereof. The present invention adopts a heat treatment process based on sub-temperature quenching, cooperates with a homemade quenching liquid and is assisted by ultrasonic action, which can significantly improve the toughness of the 35CrMo steel stud while having high strength; further combined with a laser cladding surface treatment process, the surface strength, wear resistance, high temperature resistance, oxidation resistance and corrosion resistance of the steel stud can be greatly improved, thereby enabling the steel stud to meet the needs of more usage scenarios and extend its service life.
[0057] In the quenching liquid provided by the present invention, the bursting effect of the crystals precipitated from sodium chloride and sodium nitrate in the steam film stage can destroy the steam film, and the oxide scale on the surface of the workpiece is also blown up, so that the cooling capacity of the quenching liquid in the high temperature zone can be improved. The modified carbon nanotubes can improve the heat transfer coefficient of the quenching liquid, thereby improving the cooling rate. More importantly, the modified carbon nanotubes uniformly dispersed in the coolant can stably maintain uniform dispersion and form a heat transfer network under the action of the auxiliary ultrasound applied during quenching, thereby greatly improving the uniformity of cooling; on the other hand, the carbon nanotubes have the effects of inducing crystallization, reducing the crystallization activation energy, and increasing the crystallization rate, which can promote the crystallization of sodium chloride and sodium nitrate. On the one hand, the auxiliary ultrasound can maintain the stable dispersion of the modified carbon nanotubes, and on the other hand, the ultrasound has a film-breaking effect on the steam film, which can improve the cooling rate of the workpiece at high temperature; the ultrasound will excite a strong cavitation effect in the liquid, thereby generating a large number of cavitation bubbles in the liquid, and then explode and rupture, and the huge shock wave generated can destroy the steam film on the surface of the workpiece, ensuring that the quenching liquid can freely approach the surface of the workpiece, and improving the cooling rate and uniformity. The modified carbon nanotubes in the formula of the quenching liquid of the present invention, sodium chloride, sodium nitrate, and the auxiliary ultrasonic wave play a role of mutual cooperation and synergy in improving the quenching effect; in addition, the quenching liquid of the present invention has the characteristics of being non-toxic, smokeless, and non-combustible. Compared with quenching oil, it has the advantages of being safe to use and having no environmental pollution.
[0058] In the composite cladding alloy powder of the present invention, CeYO-Ni@TiCN powder and Al powder, Ti powder, and Ni powder play a role of mutual cooperation and synergistic enhancement in improving the performance of the cladding layer. In the CeYO-Ni@TiCN structural system, the coating of nickel powder can improve the wettability of TiC powder and TiN powder with other cladding powder raw materials Al powder, Ti powder, and Ni powder, so that TiC powder and TiN powder can be evenly mixed with these metal powders, and can also be evenly dispersed when forming a cladding layer. The CeYO-Ni@TiCN structural system can also better achieve the uniform dispersion of rare earth oxides CeO2 and Y2O3 in the alloy powder. Ni has good compatibility with Fe in the matrix, which can help to improve the interface bonding strength of the cladding layer. Under the high temperature of laser cladding, Ti powder can form TiC phase with C in the matrix at the interface, and intercalate at the interface to produce pinning effect, which can improve the bonding strength. The effects of rare earth oxides CeO2 and Y2O3 in promoting crystallization and inhibiting grain growth can help increase the number of TiC phases and refine grains in this process. Al powder, Ti powder and Ti in the matrix can form reinforcing phases such as TiAl during the cladding process. The intercalated reinforcing phases can improve the connection strength between the reinforced cladding layer and the matrix; Al can form an Al2O3 protective film on the surface of the cladding layer, which can prevent oxygen from entering the cladding layer and improve its antioxidant ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 is the XRD spectrum of the composite laser cladding layer prepared in Example 1;
[0060] Figure 2 The hardness test results of the stud blanks after heat treatment prepared in Example 1 and the optimized experimental example;
[0061] Figure 3 The tensile strength test results of the stud blanks after heat treatment prepared in Example 1 and the optimized experimental example;
[0062] Figure 4 The yield strength test results of the stud blanks after heat treatment prepared in Example 1 and the optimized experimental example;
[0063] Figure 5 The -40°C transverse impact energy test results of the heat-treated stud blanks prepared in Example 1 and the optimized experimental example;
[0064] Figure 6 The room temperature hardness test results of the high performance 35CrMo steel studs prepared in Examples 1-4 and Comparative Examples 1-6;
[0065] Figure 7 The hardness test results of the high-performance 35CrMo steel studs prepared in Examples 1-4 and Comparative Examples 1-6 after being kept at 600°C for 4 hours;
[0066] Figure 8 The tensile strength test results of the high performance 35CrMo steel studs prepared in Examples 1-4 and Comparative Examples 1-6;
[0067] Fig. 9 The yield strength test results of the high performance 35CrMo steel studs prepared in Examples 1-4 and Comparative Examples 1-6;
[0068] Fig.10 The test results of the room temperature wear performance of the high performance 35CrMo steel studs prepared in Examples 1-4 and Comparative Examples 1-6;
[0069] Fig.11 The high temperature wear performance test results of the high performance 35CrMo steel studs prepared in Examples 1-4 and Comparative Examples 1-6; DETAILED DESCRIPTION
[0070] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0071] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0072] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0073] The present invention provides a high-performance 35CrMo steel stud based on a sub-temperature quenching process, which comprises a steel stud body and a composite laser cladding layer arranged on the surface of the steel stud body;
[0074] The composition of the steel stud body is calculated by mass percentage:
[0075] C: 0.32-0.40%, Si: 0.17-0.35%, Mn: 0.42-0.63%, Cr: 0.93-1.08%, Mo: 0.17-0.25%, Ni: 0.14-0.28%, Ti: 0.09-0.25%, the balance is Fe and unavoidable impurities;
[0076] The steel stud body is obtained by melting, casting, heat treatment based on sub-temperature quenching and machining. The composite laser cladding layer is prepared on the steel stud body by laser cladding process using composite cladding alloy powder as cladding material.
[0077] The present invention also provides a method for preparing a high-performance 35CrMo steel stud based on the above sub-temperature quenching process, comprising the following steps:
[0078] S1. Melting:
[0079] Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1450-1550℃ for 30-50min, slag off, LF refining, the refining temperature is 1520-1580℃, and the insulation time is 8-20min;
[0080] S2, casting: casting at 1400-1450°C to obtain a stud blank;
[0081] S3. Heat treatment based on sub-temperature quenching:
[0082] S3-1, high temperature normalizing and tempering: normalize the stud blank at 900-1000℃ for 1.5-4h, then cool to 500-600℃, temper for 2-6h, add to quenching liquid, and quench to room temperature with ultrasonic assistance;
[0083] S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace, kept warm for 35 minutes, then added to the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 550-600°C for 1-4 hours, and air-cooled to room temperature to obtain a heat-treated stud blank;
[0084] In a preferred embodiment, the composition of the quenching liquid is as follows by weight: 0.25% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water. The preparation method of the quenching liquid is as follows:
[0085] 2 g of multi-walled carbon nanotubes were added to 100 mL of a mixed acid consisting of 95% by mass sulfuric acid and 60% by mass nitric acid in a volume ratio of 2:1, heated under reflux at 80°C for 12 h, cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 12 h to obtain modified carbon nanotubes;
[0086] According to the mass ratio, the modified carbon nanotubes were first added into deionized water and ultrasonically dispersed for 60 minutes. Then, sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol were added under continuous stirring at 800 rpm and ultrasonically dispersed for 30 minutes to obtain a quenching solution.
[0087] S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate;
[0088] S5. Laser cladding treatment:
[0089] After preheating the stud intermediate, composite cladding alloy powder is used as cladding material. A composite laser cladding layer is prepared on the surface of the preheated stud intermediate by synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud.
[0090] In a preferred embodiment, the raw materials of the composite cladding alloy powder include, by weight percentage:
[0091] CeYO-Ni@TiCN powder 68-73%, Al powder 4.2-5.5%, Ti powder 5.8-7.4%, and the balance Ni powder.
[0092] The preparation method of the composite cladding alloy powder is as follows:
[0093] Al powder, Ti powder, Ni powder and CeYO-Ni@TiCN powder were added into a ball mill and ball milled for 8 h at 500 rpm under nitrogen protection. The ball-to-material ratio was 8:1. After the ball milling, the composite cladding alloy powder was obtained.
[0094] Among them, the particle sizes of Al powder, Ti powder and Ni powder are all 0.5-5 μm.
[0095] Among them, CeYO-Ni@TiCN powder is prepared by the following method:
[0096] 1) Ceramic particle pretreatment
[0097] TiC powder and TiN powder are respectively added to nitric acid with a concentration of 50-65wt%, ultrasonically treated for 15-60min, filtered, washed with deionized water until neutral, and then vacuum dried at 80-110°C to constant weight to obtain pretreated TiC powder and TiN powder;
[0098] 2) 0.65-2.62 g of pretreated TiC powder and 0.98-3.94 g of pretreated TiN powder were added to 50-200 mL of 0.25-1 mol / L NiCl2 solution, and then 4.6-18.4 mL of 0.05-0.2 mol / L CeCl3 solution and 11.2-44.8 mL of 0.05-0.2 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 30-90 min, and then the pH value was adjusted to 5-6 with 10-25 wt% hydrochloric acid;
[0099] 3) Under continuous stirring at 100-400 rpm, 65-260 mL of a 0.25-1 mol / L (NH4)2C2O4 solution is added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system is controlled to 50-60°C, the addition is completed within 1-4 hours, and then the reaction is continued for 1.5-4 hours, filtered, the solid product is washed with deionized water until neutral, and vacuum dried at 80-100°C to constant weight to obtain a precursor;
[0100] 4) calcining the precursor in a hydrogen atmosphere at 650-720° C. for 1.5-6 h, and grinding to obtain CeYO-Ni@TiCN powder.
[0101] In a preferred embodiment, in step S3-2, the heating and holding procedure of the sub-temperature quenching is: heating to 765°C at a rate of 18°C / min, holding for 10 minutes, heating to 782°C, holding for 20 minutes, cooling to 770°C, holding for 5 minutes;
[0102] In step S3-1, the ultrasonic power for auxiliary quenching is 400-800W, and the ultrasonic frequency is 15-23kHz.
[0103] In step S3-2, the ultrasonic power for auxiliary quenching is 600-1000W, and the ultrasonic frequency is 18-24kHz.
[0104] 35CrMo steel has excellent comprehensive properties, for example, high mechanical strength, impact toughness and high fatigue limit, high creep strength and endurance strength at high temperature, and can be used to prepare fasteners, such as studs, nuts, screws, etc. In order to further improve the comprehensive properties of 35CrMo steel studs, the present invention has been improved in the following aspects.
[0105] On the one hand, the use of heat treatment based on sub-temperature quenching can improve the impact toughness of steel, and at the same time can obtain higher strength. Sub-temperature quenching refers to quenching in a temperature range slightly lower than the lower limit of the material quenching temperature, sub-temperature quenching of steel, and obtaining a ferrite structure with a small amount of dispersed distribution retained on the martensite substrate. Its advantages can be summarized as follows: First, the impact toughness of steel at room temperature and low temperature is improved, thereby expanding the scope of use of the material; second, the cold brittle transition temperature of steel is reduced, and the material can be in a tough state at a lower temperature; third, the reversible tempering brittleness of steel is suppressed, so the tempering temperature of the quenched and tempered part can be reduced to restore the strength, thereby obtaining high toughness without sacrificing strength (Gao Huilin, Wang Yu. Petroleum Engineering Materials. Northwestern Polytechnical University Press. 2011). In the present invention, in conjunction with the heat treatment process of high temperature normal tempering and sub-temperature quenching-tempering, part of quasi-polygonal ferrite is introduced into the steel and the precipitation of nano-scale carbides in the tempered structure is promoted, which can improve its toughness and have higher strength.
[0106] Secondly, in the quenching process, the use of homemade quenching liquid and ultrasonic-assisted technology can obtain a suitable cooling rate and improve cooling uniformity, which is conducive to obtaining finer and more uniform grains compared to conventional quenching processes, improving organizational uniformity, thereby further improving the quenching effect and helping to improve the overall performance of steel.
[0107] The cooling process of the workpiece in the quenching liquid can generally be divided into three stages: the steam film stage, the boiling stage and the convection cooling stage. When water is used as the coolant, the steam film generated by gasification in the steam film stage prevents the heat dissipation of the workpiece, the cooling speed is not fast enough, and it is easy to cause uneven cooling of the workpiece surface and soft spots. In the present invention, the bursting effect of the crystals precipitated from sodium chloride and sodium nitrate in the steam film stage can destroy the steam film, and the oxide scale on the surface of the workpiece is also blown up, which can improve the cooling capacity of the quenching liquid in the high temperature zone. The modified carbon nanotubes can improve the heat transfer coefficient of the quenching liquid, thereby increasing the cooling speed. More importantly, the modified carbon nanotubes uniformly dispersed in the coolant can stably maintain uniform dispersion under the action of ultrasound assisted by quenching, and form a heat transfer network, thereby greatly improving the uniformity of cooling; on the other hand, the carbon nanotubes have the effect of inducing crystallization, reducing the activation energy of crystallization, and increasing the crystallization rate, which can promote the crystallization of sodium chloride and sodium nitrate. On the one hand, the auxiliary application of ultrasound can maintain the stable dispersion of the modified carbon nanotubes. On the other hand, ultrasound has a film-breaking effect on the steam film, which can increase the cooling rate of the workpiece at high temperature. Ultrasonic waves will stimulate a strong cavitation effect in the liquid, thereby generating a large number of cavitation bubbles in the liquid, which then explode and burst. The huge shock wave generated can destroy the steam film on the surface of the workpiece, ensuring that the quenching liquid can freely approach the workpiece surface, thereby increasing the cooling rate and uniformity.
[0108] Therefore, the modified carbon nanotubes in the formula of the quenching liquid of the present invention, sodium chloride, sodium nitrate, and the auxiliary ultrasonic wave play a role of mutual cooperation and synergy in improving the quenching effect; in addition, the quenching liquid of the present invention has the characteristics of being non-toxic, smokeless, and non-combustible. Compared with quenching oil, it has the advantages of being safe to use and having no environmental pollution.
[0109] Thirdly, the present invention can greatly improve the surface strength, wear resistance, high temperature resistance and corrosion resistance of the steel stud by preparing a composite laser cladding layer on the surface of the steel stud body, thereby enabling the steel stud to meet the needs of more usage scenarios and extend its service life.
[0110] As a ceramic material, TiC has high melting point, superhardness, chemical stability, high wear resistance, and other excellent properties, which can improve the wear resistance, oxidation resistance, high temperature resistance and corrosion resistance of the laser cladding layer. TiN has high chemical stability, high wear resistance, and good oxidation resistance at high temperature. The coating formed by the compounding of TiC and TiN can obtain stronger comprehensive performance. However, the common problems encountered by TiC and TiN ceramic materials in the application of preparing cladding layers with metal doping are: poor wettability with the iron matrix, difficulty in achieving uniform dispersion, prone to uneven organization, insufficient bonding strength between the cladding layer and the matrix, etc., resulting in the difficulty in giving full play to the strengthening effect of TiC and TiN, and the performance of the obtained cladding layer is difficult to reach the expected. The present invention prepares CeYO-Ni@TiCN powder in advance, and then mixes and ball-mills it with Al powder, Ti powder, and Ni powder to prepare a composite cladding alloy powder for laser cladding, which can well solve the above problems, and can also further improve the comprehensive performance of the cladding layer. The following is a detailed description of its principle in conjunction with its preparation method.
[0111] The present invention firstly pre-treats TiC powder and TiN powder with strong acid, and then coats the surface of TiC powder and TiN powder with nickel powder by chemical co-precipitation process combined with high temperature reduction calcination. 3+ , Y 3+ with Ni 2+ Ion compounding introduces evenly dispersed rare earth oxides into the coating system, ultimately forming a rare earth oxide-doped, nickel powder-coated TiC and TiN structural system: CeYO-Ni@TiCN. The main reactions involved in the above process are as follows:
[0112] NiCl2+(NH4)2C2O4→NiC2O4↓+2NH4Cl;
[0113] 2CeCl3+3(NH4)2C2O4→Ce2(C2O4)3↓+6NH4Cl;
[0114] 2YCl3+3(NH4)2C2O4→Y2(C2O4)3↓+6NH4Cl;
[0115] NiC2O4+H2→Ni+CO2↑+CO↑+H2O;
[0116] Ce2(C2O4)3→2CeO2+3CO2↑+3CO↑;
[0117] 2Y2(C2O4)3→2Y2O3+9CO2↑+3C.
[0118] In the CeYO-Ni@TiCN structural system, the coating of nickel powder can improve the wettability of TiC powder and TiN powder with other cladding powder raw materials Al powder, Ti powder, and Ni powder, so that TiC powder and TiN powder can be evenly mixed with these metal powders and can be evenly dispersed when forming the cladding layer. The CeYO-Ni@TiCN structural system can also better achieve the uniform dispersion of rare earth oxides CeO2 and Y2O3 in the alloy powder. Ni has good compatibility with Fe in the matrix, which can help improve the interfacial bonding strength of the cladding layer. Under the high temperature of laser cladding, Ti powder can form TiC phase with C in the matrix at the interface, and embed at the interface to produce pinning effect, which can improve the bonding strength. The effects of rare earth oxides CeO2 and Y2O3 in promoting crystallization and inhibiting grain growth can help increase the number of TiC phases and refine grains in this process. Al powder, Ti powder and Ti in the matrix can form reinforcing phases such as TiAl during the cladding process. The embedded reinforcing phase can improve the connection strength between the reinforced cladding layer and the matrix; Al can form an Al2O3 protective film on the surface of the cladding layer, which can prevent oxygen from entering the cladding layer and improve its antioxidant ability.
[0119] Rare earth oxides CeO2 and Y2O3 can form stable compounds with low melting points with impurity elements (such as P and S), float to the surface in the molten pool and form slag, and in the process of floating, they can also carry the gas in the molten pool (rare earths have a strong affinity for oxygen, hydrogen, etc.), play a role in degassing, deslagging, and purifying the structure, which can help eliminate pores and cracks and increase the density of the cladding layer; in addition, rare earth oxides can also form rare earth-containing intermetallic compounds with other elements, which can play a role in refining grains, making the TiC and TiN particles after recrystallization refined, which can further improve the strength of the cladding layer.
[0120] Among them, Y2O3 is a high melting point compound, which can increase the nucleation points in the cladding layer, improve the nucleation rate, and promote the refinement of the cladding layer structure; at the same time, it can also reduce the gaps between dendrites, hinder the growth of dendrites, and further promote the uniformity and refinement of the cladding layer structure. (Yang Qingxiang, Zhao Bin, Yuan Xiao, et al. Effect of nano-Y2O3 on the surface microstructure and wear resistance of hypereutectic Fe-Cr-C cladding alloy [J]. Surface Technology, 2015, 44 (4): 7. DOI: 10.16490 / j.cnki.issn.1001-3660.2015.04.008.)
[0121] Therefore, in the composite cladding alloy powder of the present invention, CeYO-Ni@TiCN powder, Al powder, Ti powder and Ni powder play a role of mutual cooperation and synergistic enhancement in improving the performance of the cladding layer.
[0122] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0123] Sources of main raw materials:
[0124] Quenching oil, brand engi Yingji, model E-CH01, purchased from Jiangsu Yingji Lubrication Technology Co., Ltd.;
[0125] Multi-walled carbon nanotubes, diameter: 10-20 nm, inner diameter: 5-10 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0126] Sodium polyacrylate, Shanghai Hongzhuang Chemical Technology Co., Ltd.;
[0127] Polyethylene glycol-200, Shanghai Hongzhuang Chemical Technology Co., Ltd.;
[0128] Sodium chloride, Shanghai Hongzhuang Chemical Technology Co., Ltd.;
[0129] TiC powder, particle size 1 μm, Dinghong (Shanghai) New Material Technology Co., Ltd.;
[0130] TiN powder, particle size 1 μm, Dinghong (Shanghai) New Material Technology Co., Ltd.;
[0131] CeCl3, Shandong Desheng New Materials Co., Ltd.;
[0132] YCl3, Shandong Haoshun Chemical Co., Ltd.
[0133] Example 1
[0134] A high-performance 35CrMo steel stud based on a sub-temperature quenching process, comprising a steel stud body and a composite laser cladding layer arranged on the surface of the steel stud body, wherein the composition of the steel stud body is calculated by mass percentage as follows:
[0135] C: 0.37%, Si: 0.21%, Mn: 0.46%, Cr: 0.95%, Mo: 0.22%, Ni: 0.19%, Ti: 0.14%, the balance is Fe and unavoidable impurities;
[0136] The preparation method of the high-performance 35CrMo steel stud comprises the following steps:
[0137] S1. Melting;
[0138] Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1500℃ for 45min, skim off the slag, LF refining, the refining temperature is 1550℃, and the holding time is 15min;
[0139] S2, casting: casting at 1450° C. to obtain a stud blank;
[0140] S3. Heat treatment based on sub-temperature quenching:
[0141] S3-1, high temperature normalizing and tempering: the stud blank is heated to 950℃ at a rate of 20℃ / min, kept at this temperature for 2h for normalizing, then cooled to 580℃ at a rate of 15℃ / min, kept at this temperature for 4h for tempering, added to the quenching liquid, and quenched to room temperature under the assistance of ultrasound;
[0142] S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace and kept at this temperature for 35 minutes. The specific heating and holding procedure is: heating to 765°C at a rate of 18°C / min, keeping at this temperature for 10 minutes, heating to 782°C, keeping at this temperature for 20 minutes, cooling to 770°C, and keeping at this temperature for 5 minutes;
[0143] Then, the stud blank is added into the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 560°C for 2h, and air-cooled to room temperature to obtain a heat-treated stud blank;
[0144] In step S3-1, the ultrasonic power for auxiliary quenching is 650W, and the ultrasonic frequency is 18kHz.
[0145] In step S3-2, the ultrasonic power for auxiliary quenching is 800W, and the ultrasonic frequency is 22kHz.
[0146] The composition of the quenching liquid is as follows by weight: 0.25% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water. The preparation method of the quenching liquid is as follows:
[0147] 2 g of multi-walled carbon nanotubes were added to 100 mL of a mixed acid consisting of 95% by mass sulfuric acid and 60% by mass nitric acid in a volume ratio of 2:1, heated under reflux at 80°C for 12 h, cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 12 h to obtain modified carbon nanotubes;
[0148] According to the mass ratio, the modified carbon nanotubes were first added into deionized water and ultrasonically dispersed for 60 minutes. Then, sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol were added under continuous stirring at 800 rpm and ultrasonically dispersed for 30 minutes to obtain a quenching solution.
[0149] S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate;
[0150] S5. Laser cladding treatment:
[0151] The stud intermediate was heated to 200°C and kept warm for 1.5 hours. Then, the composite cladding alloy powder was used as the cladding material. The composite laser cladding layer was prepared on the surface of the preheated stud intermediate by synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud. The average thickness of the composite laser cladding layer was about 800 μm.
[0152] The laser cladding process conditions are: Ar gas is used as the protective gas, the flow rate is 10L / min, the laser power is 2.2kW, the spot diameter is 4mm, and the powder feeding amount is 15g / min.
[0153] The raw materials of the composite cladding alloy powder include, by weight percentage, 70% of CeYO-Ni@TiCN powder, 5% of Al powder, 6.5% of Ti powder, and the balance of Ni powder.
[0154] The preparation method of the composite cladding alloy powder is as follows:
[0155] Al powder, Ti powder, Ni powder and CeYO-Ni@TiCN powder were added into a ball mill and ball milled for 8 h at 500 rpm under nitrogen protection. The ball-to-material ratio was 8:1. After the ball milling, the composite cladding alloy powder was obtained.
[0156] The particle sizes of Al powder, Ti powder and Ni powder are all 2 μm.
[0157] Among them, CeYO-Ni@TiCN powder is prepared by the following method:
[0158] 1) Ceramic particle pretreatment
[0159] TiC powder with a particle size of 1 μm and TiN powder with a particle size of 1 μm were added to nitric acid with a concentration of 55 wt%, and ultrasonically treated for 40 min, filtered, washed with deionized water until neutral, and then vacuum dried at 100° C. to constant weight to obtain pretreated TiC powder and TiN powder;
[0160] 2) 1.31 g of pretreated TiC powder and 1.97 g of pretreated TiN powder were added to 100 mL of 0.5 mol / L NiCl2 solution, and then 9.2 mL of 0.1 mol / L CeCl3 solution and 22.4 mL of 0.1 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 45 min, and then the pH value was adjusted to 6 with 20 wt% hydrochloric acid;
[0161] 3) Under continuous stirring at 200 rpm, 130 mL of 0.5 mol / L (NH4)2C2O4 solution was added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system was controlled to 55°C, the addition was completed within 2 h, and then the reaction was continued for 2 h, filtered, and the solid product was washed with deionized water until neutral, and vacuum dried at 90°C to constant weight to obtain a precursor;
[0162] 4) The precursor was calcined at 680°C for 3 h in a hydrogen atmosphere and ground to obtain CeYO-Ni@TiCN powder.
[0163] Reference Figure 1 , is the XRD spectrum of the composite laser cladding layer prepared in Example 1.
[0164] Sub-temperature quenching process optimization experiment
[0165] The heat-treated stud blank is prepared according to the preparation method of Example 1, except that the quenching operations used in steps S3-1 and S3-2 are different, as follows:
[0166] Optimization Experiment Example 1-1: Using water as the quenching liquid;
[0167] Optimization Experimental Example 1-2: Commercially available quenching oil (engi Yingji, Jiangsu Yingji Lubrication Technology Co., Ltd.) was used as the quenching liquid;
[0168] Optimization Experimental Example 1-3: No ultrasonic assistance is applied in the quenching operation of steps S3-1 and S3-2.
[0169] Optimization Experimental Example 1-4: The composition of the quenching liquid is as follows by weight percentage: sodium chloride 12.0%, sodium nitrate 8.5, sodium polyacrylate 17.6%, polyethylene glycol-2009.3%, and the rest is deionized water. The preparation method is as follows: sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol are added to deionized water according to the mass ratio under continuous stirring at 800 rpm, and ultrasonically dispersed for 30 minutes to obtain a quenching liquid.
[0170] Optimization Experimental Example 1-5: The composition of the quenching liquid is as follows by weight percentage: 0.2% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water. The preparation method is the same as that of Example 1.
[0171] Optimization Experimental Example 1-6: The composition of the quenching liquid is as follows by weight percentage: 0.3% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water. The preparation method is the same as that of Example 1.
[0172] The following performance tests were performed on the heat-treated stud blanks prepared in Example 1 and the above optimized experimental examples:
[0173] Hardness: Tested in accordance with the standard GB / T4340.1-2012 "Vickers hardness test for metal materials - test method";
[0174] The tensile strength and yield strength are tested according to the standard GB / T 228.1-2010 “Room temperature tensile test of metal materials - Test method”.
[0175] Impact toughness test: refer to the standard GB / T 229-2007 "Charpy pendulum impact test method for metallic materials" to test the impact energy at -40℃.
[0176] The test results are shown in Table 1 and Figure 2-Figure 5 shown.
[0177] Table 1
[0178]
[0179]
[0180] According to Table 1 and Figure 2-5 It can be seen from the test results that the heat-treated stud blank prepared in Example 1 has high low-temperature toughness and can maintain high strength at the same time; the results of optimized experimental examples 1-1 and 1-2 show that the comprehensive performance of the stud blank obtained by quenching with the homemade quenching liquid of the present invention is better than that when water and quenching oil are used; the results of optimized experimental examples 1-3 show that ultrasonic-assisted quenching can help improve the comprehensive performance of the stud blank, and the decrease in the comprehensive performance of the stud blank in optimized experimental example 1-4 is attributed to the fact that no modified carbon nanotubes are added to the quenching liquid; the results of optimized experimental examples 1-5 and 1-6 are compared with those of Example 1, which shows that the content of modified carbon nanotubes in the quenching liquid has a certain influence on the comprehensive performance of the stud blank after quenching.
[0181] Example 2
[0182] A high-performance 35CrMo steel stud based on a sub-temperature quenching process, comprising a steel stud body and a composite laser cladding layer arranged on the surface of the steel stud body, wherein the composition of the steel stud body is calculated by mass percentage as follows:
[0183] C: 0.38%, Si: 0.24%, Mn: 0.49%, Cr: 0.94%, Mo: 0.21%, Ni: 0.18%, Ti: 0.20%, the balance is Fe and unavoidable impurities;
[0184] The preparation method of the high-performance 35CrMo steel stud comprises the following steps:
[0185] S1. Melting;
[0186] Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1500℃ for 45min, skim off the slag, LF refining, the refining temperature is 1580℃, and the holding time is 15min;
[0187] S2, casting: casting at 1450° C. to obtain a stud blank;
[0188] S3. Heat treatment based on sub-temperature quenching:
[0189] S3-1, high temperature normalizing and tempering: the stud blank is heated to 950℃ at a rate of 20℃ / min, kept at this temperature for 2h for normalizing, then cooled to 580℃ at a rate of 15℃ / min, kept at this temperature for 4h for tempering, added to the quenching liquid, and quenched to room temperature under the assistance of ultrasound;
[0190] S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace and kept at this temperature for 35 minutes. The specific heating and holding procedure is: heating to 765°C at a rate of 18°C / min, keeping at this temperature for 10 minutes, heating to 782°C, keeping at this temperature for 20 minutes, cooling to 770°C, and keeping at this temperature for 5 minutes;
[0191] Then, the stud blank is added into the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 560°C for 2h, and air-cooled to room temperature to obtain a heat-treated stud blank;
[0192] In step S3-1, the ultrasonic power for auxiliary quenching is 650W, and the ultrasonic frequency is 18kHz.
[0193] In step S3-2, the ultrasonic power for auxiliary quenching is 800W, and the ultrasonic frequency is 22kHz.
[0194] The composition of the quenching liquid is as follows by weight: 0.25% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water. The preparation method of the quenching liquid is as follows:
[0195] 2 g of multi-walled carbon nanotubes were added to 100 mL of a mixed acid consisting of 95% by mass sulfuric acid and 60% by mass nitric acid in a volume ratio of 2:1, heated under reflux at 80°C for 12 h, cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 12 h to obtain modified carbon nanotubes;
[0196] According to the mass ratio, the modified carbon nanotubes were first added into deionized water and ultrasonically dispersed for 60 minutes. Then, sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol were added under continuous stirring at 800 rpm and ultrasonically dispersed for 30 minutes to obtain a quenching solution.
[0197] S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate;
[0198] S5. Laser cladding treatment:
[0199] The stud intermediate was heated to 200°C and kept warm for 1.5 hours. Then, the composite cladding alloy powder was used as the cladding material. The composite laser cladding layer was prepared on the surface of the preheated stud intermediate by synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud. The average thickness of the composite laser cladding layer was about 800 μm.
[0200] The laser cladding process conditions are: Ar gas is used as the protective gas, the flow rate is 10L / min, the laser power is 2.2kW, the spot diameter is 4mm, and the powder feeding amount is 15g / min.
[0201] The raw materials of the composite cladding alloy powder include, by weight percentage, 70% of CeYO-Ni@TiCN powder, 5% of Al powder, 6.5% of Ti powder, and the balance of Ni powder.
[0202] The preparation method of the composite cladding alloy powder is as follows:
[0203] Al powder, Ti powder, Ni powder and CeYO-Ni@TiCN powder were added into a ball mill and ball milled for 8 h at 500 rpm under nitrogen protection. The ball-to-material ratio was 8:1. After the ball milling, the composite cladding alloy powder was obtained.
[0204] The particle sizes of Al powder, Ti powder and Ni powder are all 2 μm.
[0205] Among them, CeYO-Ni@TiCN powder is prepared by the following method:
[0206] 1) Ceramic particle pretreatment
[0207] TiC powder with a particle size of 1 μm and TiN powder with a particle size of 1 μm were added to nitric acid with a concentration of 55 wt%, and ultrasonically treated for 40 min, filtered, washed with deionized water until neutral, and then vacuum dried at 100° C. to constant weight to obtain pretreated TiC powder and TiN powder;
[0208] 2) 1.31 g of pretreated TiC powder and 1.97 g of pretreated TiN powder were added to 100 mL of 0.5 mol / L NiCl2 solution, and then 9.2 mL of 0.1 mol / L CeCl3 solution and 22.4 mL of 0.1 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 45 min, and then the pH value was adjusted to 6 with 20 wt% hydrochloric acid;
[0209] 3) Under continuous stirring at 200 rpm, 130 mL of 0.5 mol / L (NH4)2C2O4 solution was added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system was controlled to 55°C, the addition was completed within 2 h, and then the reaction was continued for 2 h, filtered, and the solid product was washed with deionized water until neutral, and vacuum dried at 90°C to constant weight to obtain a precursor;
[0210] 4) The precursor was calcined at 680°C for 3 h in a hydrogen atmosphere and ground to obtain CeYO-Ni@TiCN powder.
[0211] Example 3
[0212] A high-performance 35CrMo steel stud based on a sub-temperature quenching process, comprising a steel stud body and a composite laser cladding layer arranged on the surface of the steel stud body, wherein the composition of the steel stud body is calculated by mass percentage as follows:
[0213] C: 0.37%, Si: 0.21%, Mn: 0.46%, Cr: 0.95%, Mo: 0.22%, Ni: 0.19%, Ti: 0.19%, the balance is Fe and unavoidable impurities;
[0214] The preparation method of the high-performance 35CrMo steel stud comprises the following steps:
[0215] S1. Melting;
[0216] Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1500℃ for 45min, skim off the slag, LF refining, the refining temperature is 1550℃, and the holding time is 15min;
[0217] S2, casting: casting at 1450° C. to obtain a stud blank;
[0218] S3. Heat treatment based on sub-temperature quenching:
[0219] S3-1, high temperature normalizing and tempering: the stud blank is heated to 950℃ at a rate of 20℃ / min, kept at this temperature for 2h for normalizing, then cooled to 580℃ at a rate of 15℃ / min, kept at this temperature for 4h for tempering, added to the quenching liquid, and quenched to room temperature under the assistance of ultrasound;
[0220] S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace and kept at this temperature for 35 minutes. The specific heating and holding procedure is: heating to 765°C at a rate of 18°C / min, keeping at this temperature for 10 minutes, heating to 782°C, keeping at this temperature for 20 minutes, cooling to 770°C, and keeping at this temperature for 5 minutes;
[0221] Then, the stud blank is added into the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 560°C for 2h, and air-cooled to room temperature to obtain a heat-treated stud blank;
[0222] In step S3-1, the ultrasonic power for auxiliary quenching is 650W, and the ultrasonic frequency is 18kHz.
[0223] In step S3-2, the ultrasonic power for auxiliary quenching is 800W, and the ultrasonic frequency is 22kHz.
[0224] The composition of the quenching liquid is as follows by weight: 0.25% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water. The preparation method of the quenching liquid is as follows:
[0225] 2 g of multi-walled carbon nanotubes were added to 100 mL of a mixed acid consisting of 95% by mass sulfuric acid and 60% by mass nitric acid in a volume ratio of 2:1, heated under reflux at 80°C for 12 h, cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 12 h to obtain modified carbon nanotubes;
[0226] According to the mass ratio, the modified carbon nanotubes were first added into deionized water and ultrasonically dispersed for 60 minutes. Then, sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol were added under continuous stirring at 800 rpm and ultrasonically dispersed for 30 minutes to obtain a quenching solution.
[0227] S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate;
[0228] S5. Laser cladding treatment:
[0229] The stud intermediate was heated to 200°C and kept warm for 1.5 hours. Then, the composite cladding alloy powder was used as the cladding material. The composite laser cladding layer was prepared on the surface of the preheated stud intermediate by synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud. The average thickness of the composite laser cladding layer was about 800 μm.
[0230] The laser cladding process conditions are: Ar gas is used as the protective gas, the flow rate is 10L / min, the laser power is 2.2kW, the spot diameter is 4mm, and the powder feeding amount is 15g / min.
[0231] The raw materials of the composite cladding alloy powder include, by weight percentage, 70% of CeYO-Ni@TiCN powder, 4.7% of Al powder, 6.9% of Ti powder, and the balance of Ni powder.
[0232] The preparation method of the composite cladding alloy powder is as follows:
[0233] Al powder, Ti powder, Ni powder and CeYO-Ni@TiCN powder were added into a ball mill and ball milled for 8 h at 500 rpm under nitrogen protection. The ball-to-material ratio was 8:1. After the ball milling, the composite cladding alloy powder was obtained.
[0234] The particle sizes of Al powder, Ti powder and Ni powder are all 2 μm.
[0235] Among them, CeYO-Ni@TiCN powder is prepared by the following method:
[0236] 1) Ceramic particle pretreatment
[0237] TiC powder with a particle size of 1 μm and TiN powder with a particle size of 1 μm were added to nitric acid with a concentration of 55 wt%, and ultrasonically treated for 40 min, filtered, washed with deionized water until neutral, and then vacuum dried at 100° C. to constant weight to obtain pretreated TiC powder and TiN powder;
[0238] 2) 1.31 g of pretreated TiC powder and 1.97 g of pretreated TiN powder were added to 100 mL of 0.5 mol / L NiCl2 solution, and then 9.2 mL of 0.1 mol / L CeCl3 solution and 22.4 mL of 0.1 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 45 min, and then the pH value was adjusted to 6 with 20 wt% hydrochloric acid;
[0239] 3) Under continuous stirring at 200 rpm, 130 mL of 0.5 mol / L (NH4)2C2O4 solution was added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system was controlled to 55°C, the addition was completed within 2 h, and then the reaction was continued for 2 h, filtered, and the solid product was washed with deionized water until neutral, and vacuum dried at 90°C to constant weight to obtain a precursor;
[0240] 4) The precursor was calcined at 680°C for 3 h in a hydrogen atmosphere and ground to obtain CeYO-Ni@TiCN powder.
[0241] Example 4
[0242] A high-performance 35CrMo steel stud based on a sub-temperature quenching process, comprising a steel stud body and a composite laser cladding layer arranged on the surface of the steel stud body, wherein the composition of the steel stud body is calculated by mass percentage as follows:
[0243] C: 0.37%, Si: 0.21%, Mn: 0.46%, Cr: 0.95%, Mo: 0.22%, Ni: 0.19%, Ti: 0.14%, the balance is Fe and unavoidable impurities;
[0244] The preparation method of the high-performance 35CrMo steel stud comprises the following steps:
[0245] S1. Melting;
[0246] Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1500℃ for 45min, skim off the slag, LF refining, the refining temperature is 1550℃, and the holding time is 15min;
[0247] S2, casting: casting at 1450° C. to obtain a stud blank;
[0248] S3. Heat treatment based on sub-temperature quenching:
[0249] S3-1, high temperature normalizing and tempering: the stud blank is heated to 950℃ at a rate of 20℃ / min, kept at this temperature for 2h for normalizing, then cooled to 580℃ at a rate of 15℃ / min, kept at this temperature for 4h for tempering, added to the quenching liquid, and quenched to room temperature under the assistance of ultrasound;
[0250] S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace and kept at this temperature for 35 minutes. The specific heating and holding procedure is: heating to 765°C at a rate of 18°C / min, keeping at this temperature for 10 minutes, heating to 782°C, keeping at this temperature for 20 minutes, cooling to 770°C, and keeping at this temperature for 5 minutes;
[0251] Then, the stud blank is added into the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 560°C for 2h, and air-cooled to room temperature to obtain a heat-treated stud blank;
[0252] In step S3-1, the ultrasonic power for auxiliary quenching is 650W, and the ultrasonic frequency is 18kHz.
[0253] In step S3-2, the ultrasonic power for auxiliary quenching is 800W, and the ultrasonic frequency is 22kHz.
[0254] The composition of the quenching liquid is as follows by weight: 0.25% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water. The preparation method of the quenching liquid is as follows:
[0255] 2 g of multi-walled carbon nanotubes were added to 100 mL of a mixed acid consisting of 95% by mass sulfuric acid and 60% by mass nitric acid in a volume ratio of 2:1, heated under reflux at 80°C for 12 h, cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 12 h to obtain modified carbon nanotubes;
[0256] According to the mass ratio, the modified carbon nanotubes were first added into deionized water and ultrasonically dispersed for 60 minutes. Then, sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol were added under continuous stirring at 800 rpm and ultrasonically dispersed for 30 minutes to obtain a quenching solution.
[0257] S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate;
[0258] S5. Laser cladding treatment:
[0259] The stud intermediate was heated to 200°C and kept warm for 1.5 hours. Then, the composite cladding alloy powder was used as the cladding material. The composite laser cladding layer was prepared on the surface of the preheated stud intermediate by synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud. The average thickness of the composite laser cladding layer was about 800 μm.
[0260] The laser cladding process conditions are: Ar gas is used as the protective gas, the flow rate is 10L / min, the laser power is 2.2kW, the spot diameter is 4mm, and the powder feeding amount is 15g / min.
[0261] The raw materials of the composite cladding alloy powder include, by weight percentage, 68% of CeYO-Ni@TiCN powder, 5% of Al powder, 6.5% of Ti powder, and the balance of Ni powder.
[0262] The preparation method of the composite cladding alloy powder is as follows:
[0263] Al powder, Ti powder, Ni powder and CeYO-Ni@TiCN powder were added into a ball mill and ball milled for 8 h at 500 rpm under nitrogen protection. The ball-to-material ratio was 8:1. After the ball milling, the composite cladding alloy powder was obtained.
[0264] The particle sizes of Al powder, Ti powder and Ni powder are all 2 μm.
[0265] Among them, CeYO-Ni@TiCN powder is prepared by the following method:
[0266] 1) Ceramic particle pretreatment
[0267] TiC powder with a particle size of 1 μm and TiN powder with a particle size of 1 μm were added to nitric acid with a concentration of 55 wt%, and ultrasonically treated for 40 min, filtered, washed with deionized water until neutral, and then vacuum dried at 100° C. to constant weight to obtain pretreated TiC powder and TiN powder;
[0268] 2) 1.31 g of pretreated TiC powder and 1.97 g of pretreated TiN powder were added to 100 mL of 0.5 mol / L NiCl2 solution, and then 9.2 mL of 0.1 mol / L CeCl3 solution and 22.4 mL of 0.1 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 45 min, and then the pH value was adjusted to 6 with 20 wt% hydrochloric acid;
[0269] 3) Under continuous stirring at 200 rpm, 130 mL of 0.5 mol / L (NH4)2C2O4 solution was added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system was controlled to 55°C, the addition was completed within 2 h, and then the reaction was continued for 2 h, filtered, and the solid product was washed with deionized water until neutral, and vacuum dried at 90°C to constant weight to obtain a precursor;
[0270] 4) The precursor was calcined at 680°C for 3 h in a hydrogen atmosphere and ground to obtain CeYO-Ni@TiCN powder.
[0271] Comparative Example 1
[0272] This example is basically the same as Example 1, except that: in this example, the raw materials of the composite cladding alloy powder include, by weight percentage:
[0273] Ce powder 0.7%, Y powder 1.05%, TiC powder 14%, TiN powder 21%, Al powder 5%, Ti powder 6.5%, and the balance Ni powder;
[0274] The preparation method of the composite cladding alloy powder is as follows:
[0275] Ce powder, Y powder, TiC powder, TiN powder, Al powder, Ti powder and Ni powder were added into a ball mill, and ball milled for 8 hours at 500 rpm under nitrogen protection, with a ball-to-material ratio of 8:1. After the ball milling, composite cladding alloy powder was obtained;
[0276] The particle sizes of Al powder, Ti powder and Ni powder are all 2 μm, and the particle sizes of TiC powder and TiN powder are all 1 μm.
[0277] Comparative Example 2
[0278] This example is basically the same as Example 1, except that in this example, CeCl3 solution and YCl3 solution are not added in step 2) of preparing CeYO-Ni@TiCN powder.
[0279] Comparative Example 3
[0280] This example is basically the same as Example 1, except that in this example, CeCl3 solution is not added in step 2) of preparing CeYO-Ni@TiCN powder, and the added volume of YCl3 solution is 31.6 mL, and the concentration is still 0.1 mol / L.
[0281] Comparative Example 4
[0282] This example is basically the same as Example 1, except that in this example, no YCl3 solution is added in step 2) of preparing CeYO-Ni@TiCN powder, and the added volume of CeCl3 solution is 31.6 mL, and the concentration is still 0.1 mol / L.
[0283] Comparative Example 5
[0284] This example is basically the same as Example 1, except that in this example, no TiN powder is added in step 2) of preparing CeYO-Ni@TiCN powder, and the amount of TiC powder added is 3.28 g.
[0285] Comparative Example 6
[0286] This example is basically the same as Example 1, except that in this example, TiC powder is not added in step 2) of preparing CeYO-Ni@TiCN powder, and the amount of TiN powder added is 3.28 g.
[0287] The high performance 35CrMo steel studs prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to the following performance tests:
[0288] 1. Hardness
[0289] The MHV2000 microhardness tester was used to test the hardness at room temperature (25°C) and after being stored at high temperature (600°C) for 4 hours in accordance with the standard GB / T4340.1-2012 "Vickers hardness test for metallic materials - test method".
[0290] 2. Tensile properties
[0291] The tensile strength (room temperature) and yield strength (room temperature) are tested with reference to the standard GB / T 228.1-2010 "Room temperature tensile test of metallic materials - test method".
[0292] 3. Wear resistance
[0293] Room temperature non-lubricated friction and wear tests were carried out on a MS-T3000 friction and wear tester. The material of the grinding pair was SiC, the load was 100N, the rotation speed was 400r / min, the rotation radius was 3mm, and the time was 60min. Acetone was used for ultrasonic cleaning before and after the wear test, and the wear quality (mass before wear-mass after wear) was measured at room temperature (25℃) and high temperature (600℃), respectively.
[0294] The test results are shown in Table 2 and Figure 6-Figure 11 shown.
[0295] Table 2
[0296]
[0297]
[0298] According to Table 2 and Figure 5-11 It can be seen from the test results that the high-performance 35CrMo steel studs prepared in Examples 1-4 have very high surface hardness and wear resistance, and can maintain high hardness and wear resistance even at high temperatures; in Comparative Example 1, Ce powder, Y powder, TiC powder, TiN powder, Al powder, Ti powder, and Ni powder are directly ball-milled and mixed as cladding powder materials, and the CeYO-Ni@TiCN system in Example 1 is not formed, and it is difficult to overcome the defects of TiC powder and TiN powder such as difficulty in dispersion, resulting in a significant decrease in hardness, wear resistance and high temperature resistance; the comprehensive performance of Comparative Examples 2-4 is worse than that of Example 1, which can illustrate the effect of introducing rare earth oxides CeO2 and Y2O3 into the CeYO-Ni@TiCN system on the improvement of the comprehensive performance of the cladding layer, and any one of CeO2 and Y2O3 is not as good as the effect of the composite use of the two when doped alone; the results of Comparative Examples 5-6 can illustrate that the comprehensive performance of the cladding layer obtained by adding TiC powder or TiN powder alone is worse than that of the cladding layer obtained by the composite use of the two.
[0299] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing high-performance 35CrMo steel studs based on a sub-temperature quenching process, characterized in that: The following steps are involved: S1. Melting: Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1450-1550℃ for 30-50min, slag off, LF refining, the refining temperature is 1520-1580℃, and the insulation time is 8-20min; S2, casting: casting at 1400-1450°C to obtain a stud blank; S3. Heat treatment based on sub-temperature quenching: S3-1, high temperature normalizing and tempering: normalize the stud blank at 900-1000℃ for 1.5-4h, then cool to 500-600℃, temper for 2-6h, add to quenching liquid, and quench to room temperature with ultrasonic assistance; S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace, kept warm for 35 minutes, then added to the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 550-600°C for 1-4 hours, and air-cooled to room temperature to obtain a heat-treated stud blank; S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate; S5. Laser cladding treatment: After preheating the stud intermediate, composite cladding alloy powder is used as cladding material, and a composite laser cladding layer is prepared on the surface of the preheated stud intermediate by synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud; The composition of the quenching liquid is as follows by weight percentage: 0.25% of modified carbon nanotubes, 12.0% of sodium chloride, 8.5% of sodium nitrate, 17.6% of sodium polyacrylate, 9.3% of polyethylene glycol-200, and the rest is deionized water; The preparation method of the quenching liquid is: 2 g of multi-walled carbon nanotubes were added to 100 mL of a mixed acid consisting of 95% by mass sulfuric acid and 60% by mass nitric acid in a volume ratio of 2:1, heated under reflux at 80°C for 12 h, cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 12 h to obtain modified carbon nanotubes; According to the mass ratio, the modified carbon nanotubes were first added into deionized water, and ultrasonically dispersed for 60 minutes, and then sodium chloride, sodium nitrate, sodium polyacrylate and polyethylene glycol were added under continuous stirring at 800 rpm, and ultrasonically dispersed for 30 minutes to obtain the quenching liquid; The raw materials of the composite cladding alloy powder include, by weight percentage: CeYO-Ni@TiCN powder 68-73%, Al powder 4.2-5.5%, Ti powder 5.8-7.4%, and the balance Ni powder; CeYO-Ni@TiCN powder was prepared by the following method: 1) Ceramic particle pretreatment TiC powder and TiN powder are respectively added to nitric acid with a concentration of 50-65wt%, ultrasonically treated for 15-60min, filtered, washed with deionized water until neutral, and then vacuum dried at 80-110°C to constant weight to obtain pretreated TiC powder and TiN powder; 2) 0.65-2.62 g of pretreated TiC powder and 0.98-3.94 g of pretreated TiN powder were added to 50-200 mL of 0.25-1 mol / L NiCl2 solution, and then 4.6-18.4 mL of 0.05-0.2 mol / L CeCl3 solution and 11.2-44.8 mL of 0.05-0.2 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 30-90 min, and then the pH value was adjusted to 5-6 with 10-25 wt% hydrochloric acid; 3) Under continuous stirring at 100-400 rpm, 65-260 mL of a 0.25-1 mol / L (NH4)2C2O4 solution is added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system is controlled to 50-60°C, the addition is completed within 1-4 hours, and then the reaction is continued for 1.5-4 hours, filtered, the solid product is washed with deionized water until neutral, and vacuum dried at 80-100°C to constant weight to obtain a precursor; 4) calcining the precursor in a hydrogen atmosphere at 650-720° C. for 1.5-6 h, and grinding to obtain CeYO-Ni@TiCN powder.
2. The method for preparing high-performance 35CrMo steel studs based on sub-temperature quenching process according to claim 1 is characterized in that: The preparation method of the composite cladding alloy powder is: Al powder, Ti powder, Ni powder and CeYO-Ni@TiCN powder were added into a ball mill, and ball milled for 8 hours at 500 rpm under nitrogen protection, with a ball-to-material ratio of 8:
1. After the ball milling, the composite cladding alloy powder was obtained; Among them, the particle sizes of Al powder, Ti powder and Ni powder are all 0.5-5 μm.
3. The method for preparing high-performance 35CrMo steel studs based on sub-temperature quenching process according to claim 2 is characterized in that: CeYO-Ni@TiCN powder was prepared by the following method: 1) Ceramic particle pretreatment TiC powder with a particle size of 1-3 μm and TiN powder with a particle size of 1-3 μm were added to nitric acid with a concentration of 55 wt%, and ultrasonically treated for 40 min, filtered, washed with deionized water until neutral, and then vacuum dried at 100° C. to constant weight to obtain pretreated TiC powder and TiN powder; 2) 1.31 g of pretreated TiC powder and 1.97 g of pretreated TiN powder were added to 100 mL of 0.5 mol / L NiCl2 solution, and then 9.2 mL of 0.1 mol / L CeCl3 solution and 22.4 mL of 0.1 mol / L YCl3 solution were added, and ultrasonic dispersion was performed for 45 min, and then the pH value was adjusted to 6 with 20 wt% hydrochloric acid; 3) Under continuous stirring at 200 rpm, 130 mL of 0.5 mol / L (NH4)2C2O4 solution was added dropwise to the mixed solution obtained in step 2), the temperature of the reaction system was controlled to 55°C, the addition was completed within 2 h, and then the reaction was continued for 2 h, filtered, and the solid product was washed with deionized water until neutral, and vacuum dried at 90°C to constant weight to obtain a precursor; 4) The precursor was calcined at 680°C for 3 h in a hydrogen atmosphere and ground to obtain CeYO-Ni@TiCN powder.
4. The method for preparing high-performance 35CrMo steel studs based on sub-temperature quenching process according to claim 1, characterized in that: The following steps are involved: S1. Melting; Weigh the raw materials according to the composition ratio of the steel stud body, then add the raw materials into the melting furnace, melt at 1500℃ for 45min, skim off the slag, LF refining, the refining temperature is 1550℃, and the holding time is 15min; S2, casting: casting at 1450° C. to obtain a stud blank; S3. Heat treatment based on sub-temperature quenching: S3-1, high temperature normalizing and tempering: the stud blank is heated to 950℃ at a rate of 20℃ / min, kept at this temperature for 2h for normalizing, then cooled to 580℃ at a rate of 15℃ / min, kept at this temperature for 4h for tempering, added to the quenching liquid, and quenched to room temperature under the assistance of ultrasound; S3-2, sub-temperature quenching-tempering: the stud blank obtained in step S3-1 is heated to 760-785°C in a quenching furnace, kept warm for 35 minutes, then added to the quenching liquid, quenched to room temperature under the assistance of ultrasound, and finally tempered at 560°C for 2 hours, and air-cooled to room temperature to obtain a heat-treated stud blank; S4, machining: the heat-treated stud blank is subjected to precision turning, and then thread rolling and grinding to obtain a stud intermediate; S5. Laser cladding treatment: The stud intermediate was heated to 200°C and kept warm for 1.5 hours. Then, a composite cladding alloy powder was used as the cladding material. A composite laser cladding layer was prepared on the surface of the preheated stud intermediate by a synchronous powder feeding laser cladding process to obtain a high-performance 35CrMo steel stud. The laser cladding process conditions are: Ar gas is used as the protective gas, the flow rate is 10L / min, the laser power is 2.2kW, the spot diameter is 4mm, and the powder feeding amount is 15g / min.
5. The method for preparing high-performance 35CrMo steel studs based on sub-temperature quenching process according to claim 4 is characterized in that: In step S3-2, the heating and holding program of the sub-temperature quenching is: heating to 765°C at a rate of 18°C / min, holding for 10 minutes, heating to 782°C, holding for 20 minutes, cooling to 770°C, holding for 5 minutes; In step S3-1, the ultrasonic power for auxiliary quenching is 400-800W, and the ultrasonic frequency is 15-23kHz; In step S3-2, the ultrasonic power for auxiliary quenching is 600-1000W, and the ultrasonic frequency is 18-24kHz.
6. A high performance 35CrMo steel stud based on sub-temperature quenching process, characterized in that: It is prepared by the method according to any one of claims 1 to 5, and comprises a steel stud body and a composite laser cladding layer arranged on the surface of the steel stud body; The composition of the steel stud body is calculated by mass percentage: C: 0.32-0.40%, Si: 0.17-0.35%, Mn: 0.42-0.63%, Cr: 0.93-1.08%, Mo: 0.17-0.25%, Ni: 0.14-0.28%, Ti: 0.09-0.25%, the balance is Fe and unavoidable impurities; The steel stud body is obtained by melting, casting, heat treatment based on sub-temperature quenching and machining, and the composite laser cladding layer is prepared on the steel stud body by a laser cladding process using composite cladding alloy powder as a cladding material.
Citation Information
Patent Citations
A processing method for refining the grain size of 35CrMo alloy steel
CN108823361B
Q460GJEZ35 building structure steel plate and production method thereof
CN111575579A
9% Ni steel super-large-sized rotor forging applied to ultralow-temperature engineering and preparation method thereof
CN112680663A